Perception Analysis of Fisheries Business Actor on Performance of Fisheries Instructor in Bontoa District, Maros Regency - Febri, Febri (FAPETKAN UNTAD, 2019)
This study aims to determine the perception of fisheries business operators on the performance of fisheries extension workers needed by fisheries business operators in Bontoa District, Maros Regency. The method used is descriptive survey method with a purposive sampling approach. The results obtained indicate that the existence of fisheries extension workers in the Bontoa District of Maros Regency is still highly expected by fisheries businesses in this region, so that fisheries extension workers must have the ability, and be prepared to respond to the needs of fisheries business operators. In addition, fisheries instructors must be able to master and utilize information, communication and education technology, so that its existence has meaning for fisheries businesses in their working area. The method of fisheries extension that is in demand by fishery business actors from fisheries extension is to provide examples of businesses that have succeeded as a form of motivation for fisheries businesses to improve the production capabilities of fisheries businesses in Bontoa District, Maros Regency.